Effect of Early and Delayed Commencement of Paricalcitol in Combination with Enalapril on the Progression of Experimental Polycystic Kidney Disease - Priyanka S. Sagar (MDPI AG, 2021)
Vitamin D secosteroids are intranuclear regulators of cellular growth and suppress the renin-angiotensin system. The aim of this study was to test the hypothesis that the vitamin D receptor agonist, paricalcitol (PC), either alone or with enalapril (E) (an angiotensin-converting enzyme inhibitor), reduces the progression of polycystic kidney disease. Preventative treatment of Lewis polycystic kidney (LPK) and Lewis control rats with PC (0.2 μg/kg i.p. 5 days/week) or vehicle from postnatal weeks 3 to 10 did not alter kidney enlargement. To evaluate the efficacy in established disease, LPK rats received either PC (0.8 μg/kg i.p; 3 days/week), vehicle, E (50 mg/L in water) or the combination of PC + E from weeks 10 to 20. In established disease, PC also did not alter the progression of kidney enlargement, kidney cyst growth or decline in renal function in LPK rats. Moreover, the higher dose of PC was associated with increased serum calcium and weight loss. However, in established disease, the combination of PC + E reduced systolic blood pressure and heart-body weight ratio compared to vehicle and E alone (p < 0.05). In conclusion, the combination of PC + E attenuated cardiovascular disease but caused hypercalcaemia and did not alter kidney cyst growth in LPK rats.